Survival Significance of Patients With Low Prostate-Specific Antigen and High-Grade Prostate Cancer After Radical Prostatectomy, External Beam Radiotherapy, or External Beam Radiotherapy With Brachytherapy - Guo, Yadong; Mao, Shiyu; Zhang, Aihong; Zhang, Junfeng; Wang, Longsheng; Wang, Ruiliang; Zhang, Wentao; Zhang, Ziwei; Wu, Yuan; Cao, Xuan; Yang, Bin; Yao, Xudong (Frontiers in Oncology, 2019)
Objective: This study compared survival of prostate cancer patients with low prostate specific antigen level (PSA ≤10 ng/ml) and high-grades of Gleason score (GS) of 8-10 with different treatment options (i.e. radical prostatectomy [RP], external beam radiotherapy [EBRT], or external beam radiotherapy with brachytherapy [EBRT+BT]). Materials and Methods: The Surveillance, Epidemiology and End Results database data (2004-2013), and overall survival (OS) and prostate cancer-specific mortality (PCSM) were evaluated using the Cox proportional hazards regression model and Fine and Gray competing risk model. Results: The SEER data contained 9,114 patients, 4,175 of whom received RP, 4,114 received EBRT, and 825 received EBRT+BT with a median follow-up duration of 47 months. RP patients had significantly better OS than patients with EBRT and EBRT+BT (adjusted HR [AHR]: 3.36, 95% CI: 2.43-4.64, P<0.001; AHR: 2.15, 95% CI: 1.32-3.48, P=0.002; respectively). There was no statistical difference in PCSM between RP and EBRT+BT (AHR: 1.31, 95% CI: 0.61-2.80, P=0.485), while EBRT had worse OS (P<0.05). The subgroup analysis revealed that there was no statistical difference in prognosis of patients with age of >70 years old, or PSA levels of ≤2.5 ng/ml between RP and EBRT+BT (P>0.05). Conclusion: RP patients with low PSA levels and high GS had better OS compared to either EBRT or EBRT+BT, while RP and EBRT+BT resulted in significantly lower PCSM, compared to EBRT. Moreover, EBRT+BT and RP were associated with similar survival of patients with age of > 70 years old, or PSA levels of ≤ 2.5 ng/ml.